1982
DOI: 10.1007/bf02411232
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin effects on isolated bone cells

Abstract: Calcitonin decreased calcium uptake in specific rat bone cell populations obtained by sequential collagenase digestions of calvaria. The calcitonin effect on calcium uptake was observed in the same populations that manifested calcitonin-induced increases in cyclic AMP as well as high levels of acid phosphatase and the ability to release 45Ca from prelabeled devitalized bone. No effect of calcitonin was observed in cell populations that had high levels of alkaline phosphatase and lacked the potential to resorb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Again, osteoblast-like cells were found to be located deeper in the bone. Due to the anatomic position of cells in fetal and neonatal rodent calvaria, both of these methods allow an enrichment for distinct cell types, as also confirmed by other groups [11][12][13][14]. Since it has not been possible to identify osteoblasts in culture by simple microscopic examination, Luben et al [15] have suggested characterizing cultured bone cells by their biochemical properties and hormone responsiveness.…”
mentioning
confidence: 87%
“…Again, osteoblast-like cells were found to be located deeper in the bone. Due to the anatomic position of cells in fetal and neonatal rodent calvaria, both of these methods allow an enrichment for distinct cell types, as also confirmed by other groups [11][12][13][14]. Since it has not been possible to identify osteoblasts in culture by simple microscopic examination, Luben et al [15] have suggested characterizing cultured bone cells by their biochemical properties and hormone responsiveness.…”
mentioning
confidence: 87%
“…However, these studies indicate their modes of action on isolated bone cells are not identical. We have previously shown that in osteoclastic cells, CT decreases calcium uptake and increases cAMP with no effect on calcium uptake or cAMP production in osteoblastic populations [10]. By contrast, BL-5583 decreased calcium uptake in all populations of cells and did not increase cAMP levels in any bone cell population.…”
Section: Discussionmentioning
confidence: 90%
“…period; III and IV obtained after the third and fourth periods, respectively. Populations I and II were previously characterized osteoclastic by high acid phosphatase levels and the ability to resorb devitalized bone in vitro [10]. Populations III and IV were characterized osteoblastic by high alkaline phosphatase levels and the lack of in vitro resorptive ability [10].…”
Section: Homogeneous Bone Cell Isolation Proceduresmentioning
confidence: 98%
See 1 more Smart Citation
“…The first two populations (I and II) released in a series of four 15-min collagenase digestions had properties distinct from the populations (III and IV) released during the last 2 collagenase incubation periods [16]. Populations I and II had acid phosphatase levels higher than III and IV, responded to calcitonin with an increase in cyclic AMP, and resorbed devitalized bone in vitro.…”
Section: Studies With Characterized Bone Cell Populationsmentioning
confidence: 97%